CLASSIFICATION ANALYSIS OF THE PROFESSIONS OF POWER SUPPLY WORKERS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article provides information about the types of directions in the work activities of Electrical Workers and the types of damage that occur in them.